Identifying the Sources of Instabilities in Macroeconomic Fluctuations - Inoue, Atsushi; Rossi, Barbara (The Review of Economics and Statistics, 2011)
This paper investigates the sources of the substantial decrease in output growth volatility in the mid-1980s by identifying which of the structural parameters in a representative New Keynesian and structural VAR models changed. Overturning conventional wisdom, we show that the Great Moderation was due not only to changes in shock volatilities but also to changes in monetary policy parameters, as well as in the private sector's parameters. The Great Moderation was previously attributed to good luck because the alternative sources of instabilities appear to have offsetting effects on output volatility and therefore were impossible to detect using existing techniques.